2013
DOI: 10.1002/anie.201302891
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Nanosheets of Half‐Metallic Monoclinic Vanadium Dioxide with a Thermally Induced Phase Transition

Abstract: Only the half of it: A modified intercalation-deintercalation strategy that takes advantage of the characteristic thermally induced phase transition of monoclinic VO2 has been developed for the preparation of ultrathin VO2 nanosheets. The resultant nanosheets exhibit half-metallic character and a temperature-dependent phase transition. The half-metallicity could lead to applications in spintronic nanodevices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…As VO 2 films approach nanoscale dimensions, various exotic phases have been predicted, such as half metallicity and semi-Dirac cones [60,61]. With the interface quality established and the surface well-characterized, we can now confidently study the effects of film thickness on the thermally-induced MIT.…”
Section: Resultsmentioning
confidence: 99%
“…As VO 2 films approach nanoscale dimensions, various exotic phases have been predicted, such as half metallicity and semi-Dirac cones [60,61]. With the interface quality established and the surface well-characterized, we can now confidently study the effects of film thickness on the thermally-induced MIT.…”
Section: Resultsmentioning
confidence: 99%
“…To date, delamination or exfoliation is the most commonly developed approaches to prepare lamellar inorganic materials. However, it usually requires the modification of interlamellar environment and the appropriate selection of the solvent system, whereas it always takes over one week to get highly exfoliated nanosheets due to the tedious longterm aging and sonification process [8][9][10]. Moreover, the lateral scale of two-dimensional nanosheets prepared by chemical exfoliation is highly dependent on the pristine bulk materials used and the employed violent sonification would break the nanosheets into smaller pieces than the raw bulk materials itself.…”
Section: Introductionsmentioning
confidence: 99%
“…[32] Recently, it was also found that V 2 O 3 was one new intercalation-type high-capacity anode materials with a high capacity of LIBs (≈732 mA h g −1 ) based on the ex situ XRD technology, and it also exhibited the potential for anode materials of NIBs. ), [38,39] especially graphene-like 2D ultrathin nanomaterials which result in a wealth of unprecedented functionalities, [40,41] have exhibited a large superiority for LIBs. [34] Nanomaterials have shown huge advantages for various energy storage applications because of the ultra-large specific surface area and ultra-short diffusion path of ions/electrons.…”
mentioning
confidence: 99%